Aspectos constrativos do letramento e da alfabetização bilíngue e intercultural entre as escolas Mãtyk e Tekator. - Oliveira, Jocirley de (2023)
This work is the result of a doctoral research developed in the ethnographic perspective with the Apinayé, an indigenous people who inhabit the northern region of the State of Tocantins - municipality of Tocantinópolis, speakers of the homonymous language belonging to the Macro Jê Branch of the Jê Linguistic Family, with the objective of identifying , discuss and analyze the Contrastive Aspects of Literacy and Bilingual and Intercultural Literacy Between the Mãtyk and Tekator Schools of the Apinayé São José and Mariazinha villages. Therefore, the study is justified and gains relevance as it points out possibilities of collaboration for the recognition of cultural and language diversity, in the school environment, at the same time that it is concerned with the development of learning in literacy, using of the dynamics of teaching practice. For the benefit of this, the theoretical basis of the work was based mainly on Albuquerque's research with the Apinayé people (2016), on Bilingualism and on Interculturality by Almeida (2011), on the writing of Ferreiro and Teberosky (1999), on the theoretical conceptions of Gonçalves (2009), in the proposal of Mortatti (2006), in the foundational studies of Neves (2009), in the literacy project of Kleiman (2007; 2009), in the linguistic multiplicity of Rojo (2009), and in the foundations and reflections by Soares (2007), through the National Curricular Reference for Indigenous Schools (RCNEI) and in the BNCC. Regarding the methodology, the research was collaborative and followed a qualitative, quantitative and ethnographic approach. And we used the field diary, semi-structured questionnaires, photographs, images and assessments applied to Apinayé students in the 3rd and 5th years as a basis for generating information. Through systematization and analysis of the data generated, the results achieved led us to the realization that there are differences and similarities in the teaching and learning practice of bilingual and intercultural literacy and literacy developed between the Matyk and Tekator schools. Considering also the dynamics that guided the research and based on the application of questionnaires with indigenous and non-indigenous teachers, we obtained information about the continuing education that the teachers participated, the pedagogical practice developed for the teaching of literacy and literacy. Also, through the application of structured assessments with students, we understand how learning has been built in this very important phase of Elementary School. Therefore, through the study developed, the information obtained and the reflections built, we established that there are contrasting aspects between the two schools, situated in the questions of reaffirmation of culture, in the valorization of the language, in favoring the use of previous knowledge acquired outside the school. , in the organization of teaching for the use of the first language and then the second language and in the replanning of actions for pedagogical intervention.